Causas psicosociales de violencia intrafamiliar en mujeres que acuden a la comisaría primera de la mujer y la familia del cantón riobamba, período 2008-2009 - Fajardo Minchala, Narcisa De Jesús (2010)
The main objective of this investigative work is guided toward the determination of the causes psychosocias through an investigative guide of the intra-familiar violence. The investigation is descriptive type with traverse design for the summary of information,the investigative guides were revised and carried out in woman station of the Riobamba city, during the period of study (2008-2009),of the total population a sample equivalent representative was extracted to 312 cases that were selected aleatorily.